Peran Pemerintah Daerah Provinsi Riau dalam Pengelolaan Daerah Aliran Sungai Siak: Studi Kasus Daerah Hilir Daerah Aliran Sungai Siak Tahun 2010-2013 - Reski Lestari; Muhammad Ridwan (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2014)
This reseacrh is aimed to figure out how is the role of Riau Province Local Government on Siak Watershed Management (known as Daerah Aliran Sungai, DAS). It is focused to the downstream watershed of Siak River area which located in Palas Village (Kampar Regency)- Pekanbaru City- Perawang Town (Siak Regency)- Siak Sri Indrapura Town and comes down in Tanjung Belit Village (Apit river, Siak Regency), considering to the most complex problem exists on it. Those problems consist of domestic waste, industry waste, residential issue. The main objective of this research is how the role of Riau ProvinceLocal Government on DAS management and learn what the factors influnce it. The research is aimed to analyze the role of Local Government in the Province of Riau on DAS management. The type of this reseacrh is description, which means the researcher gives a description or illustration about related phenomenon or social symptom which is analyzed by describing independent variable systematicly and accurately. Data collection method is done by Indepth Interview, partisipative observation and documnetation study. The result of analysis shows that the role of local government on DAS management of downstream is based on Main Duty and Fuctionof each Departement. Department of Planning Development Region (knowns as Badan Perencanaan Pembangunan Daerah, Bappeda) Riau Province has a role on planning development, Departement of Living Environment (known as Badan Lingkungan Hidup, BLH) has a role on managing industry and domestic waste, Departement of Public Project (known as Dinas Pekerja Umum, PU) Riau Province Resicence Division has a role on resident management. A department of Local Doverment and others is low coordination and cooperation on management implementation, while cooperation of each department is needed on DAS management.